Presenting the educational policy model of skill learning for first year high school students: with a mixed approach - Keshmiri, Samaneh; Khorshidi, Abbas; Araghiyeh, Alireza; Barzegar, Nader; Doshmanziari, Esfandiar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Students can better understand what they have learned and prepare to build a better future. The present research was conducted to provide a model of educational policy for skill learning of first-year high school students. Methods: In terms of the applied goal, this research was exploratory mixed (qualitative-quantitative) in terms of data, and in terms of nature, in the qualitative dimension, it was a systemic (paradigm) foundation data, and in the quantitative dimension, it was a cross-sectional survey. The statistical population of the qualitative part included university professors and experts who had papers in the field of skill training, and in the quantitative part, it included all the teachers of the first year of secondary education in the central province who had a master’s degree and above in the field of educational sciences, numbering 500 people. The sampling method in the qualitative part is purposeful and theoretical, and with the number of 15 experts, the theoretical saturation was reached. In the quantitative part of the sample size, 217 people were selected based on Morgan’s volume determination formula. In the current research, after the open and axial coding of the measurement tool, it was sent in the form of a set form and sent to experts for selective coding and validation. Based on this, a researcher-made questionnaire was designed and distributed among the randomly selected statistical sample. Then the collected data were analyzed using descriptive and inferential statistics. Results: As a result, 5 dimensions, 20 components and 118 indicators were finalized for the educational policy model of students’ skill learning. Conclusion: After the final approval and prioritization of the experts, the dimensions, components and indicators of the model were drawn, and the experts again validated the said model.